Novel porous silica encapsulated Au nanoreactors as peroxidase mimic for one-pot glucose detection - Samanta, Anupam; Dhar, Basab B.; Devi, R. Nandini (New Journal of Chemistry, 2012)
The peroxidase family of natural enzymes facilitate H2O2 reduction by one electron transfer through aromatic substrates, if chromogenic, they can be used in the colorimetric detection of H2O2 and subsequently glucose in tandem with glucose oxidase. Au nanoparticles encapsulated within porous silica exhibited peroxidase mimetic activity and kinetic parameter evaluation indicates an excellent affinity for H2O2. It is also shown to have a detection capability for glucose in very low concentrations and could be used for glucose detection in a one-pot assay. The material is synthesised by using cation-ended thiol-stabilised ultra small gold clusters as precursors. Removal of the thiols creates micropores within the silica, making this material unique in that the active centres are protected inside the silica, yet are accessible to reactant molecules. This characteristic makes the material ideal as a detection tool where attrition resistance will be advantageous.